Metal, metal oxide and polymeric nanoformulations for the inhibition of bacterial quorum sensing. Issue 1 (January 2023) - Alavi, Mehran; Li, Li; Nokhodchi, Ali
Highlights: Virulence properties and biofilm formation of bacteria are orchestrated by QS systems. Bare metal NPs compared with functionalized ones have low efficiency for blockage of QS. Functionalization by natural metabolites should be an effective biocompatible formulation. Hydrolysis of autoinducers of QS by imprinted polymeric NPs is an efficient way to hinder resistant bacteria. Abstract: Antibiotic resistance of bacteria has caused a significant public health challenge and economic problem, resulting in a necessity to find efficient antibacterial agents. Conventional bactericidal agents hinder the growth of bacteria by slowing down the cell wall synthesis or disturbing bacterial DNA replication, protein production or other bacterial cellular metabolism that can augment natural selection pressure for turning up new antibiotic-resistant strains. Virulence properties and biofilm formation of bacteria are orchestrated by quorum-sensing systems. These quorum-sensing systems normally control antimicrobial production; and targeting these systems using metal-based nanoparticles or polymeric nanoparticles can be considered as powerful antibacterial treatments owing to their specific physicochemical and therapeutic properties. In this review, recent advances and challenges related to the inactivation of quorum-sensing systems by these nanoparticles are presented to obtain comprehensive viewpoints for future studies.